2013
DOI: 10.1210/jc.2012-3971
|View full text |Cite
|
Sign up to set email alerts
|

Elevated 1-Hour Postload Plasma Glucose Levels Identify Subjects With Normal Glucose Tolerance but Impaired β-Cell Function, Insulin Resistance, and Worse Cardiovascular Risk Profile: The GENFIEV Study

Abstract: Among subjects with NGT, those with 1-hour OGTT glucose of >155 mg/dL showed lower insulin sensitivity, impaired β-cell function, and worse cardiovascular risk profile and therefore are at greater risk of developing T2DM and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 17 publications
9
77
0
5
Order By: Relevance
“…The pathophysiological significance of elevated 1-h blood glucose levels is not (10,19,20). In subjects with NGT, an elevated 1-h glucose level is associated with insulin resistance to a degree similar to that seen among individuals with IGT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiological significance of elevated 1-h blood glucose levels is not (10,19,20). In subjects with NGT, an elevated 1-h glucose level is associated with insulin resistance to a degree similar to that seen among individuals with IGT.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated glucose levels at 1 h are associated with adverse metabolic and cardiovascular changes, reflected by body composition, cholesterol levels, and subclinical target organ damage, including arterial stiffness, carotid intimamedia thickness, and left ventricular hypertrophy (19,20,(29)(30)(31). However, very few reports of the clinical consequences have been published (32)(33)(34)(35), and although associations with macrovascular events and mortality have been shown, only one study of 1,945 subjects included glucose levels at 2 h and indicated that 1-h glucose levels predicted all-cause mortality among subjects with NGT (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] In addition, this glucose cutoff is able to identify subjects with an impaired cardiometabolic profile, characterized by high blood pressure, dyslipidemia, liver steatosis, early signs of atherosclerosis, as well as an increased mortality. [20][21][22][23][24][25] In children and adolescents, data on 1-hour postload glucose are not as extensive as in adults, but some preliminary studies have confirmed that a cutoff of 155 mg/dl, or even of 132 mg/dl, could predict future risk of T2D and identify young subjects with early cardiovascular abnormalities.…”
Section: Prediabetes and Other Earlier Forms Of Dysglycemiamentioning
confidence: 99%
“…В условиях ранней диагнос-тики повышенного артериального давления (АД) в амбулаторном и стационарном периодах медицинской помощи все большее значение приобретает наличие у пациентов различных факторов риска сердечно-сосудистых осложнений (ССО), определяющих лечеб-К Л И Н И Ц И С Т № 2'2015 О р и г и н а л ь н ы е и с с л е д о в а н и я ную тактику и индивидуальный прогноз [2,3]. Интерес представляют нарушения нутритивного статуса, угле-водного и липидного метаболизма, способствующие по результатам многочисленных исследований не толь-ко раннему дебюту артериальной гипертензии (АГ), но и активации сердечно-сосудистого континуума [4][5][6].…”
Section: Introductionunclassified